2006
DOI: 10.1117/12.661980
|View full text |Cite
|
Sign up to set email alerts
|

Diamond-like carbon films deposited onto optical fibres and waveguides: application in chemical sensing

Abstract: The paper presents the diamond-like carbon (DLC) film as a coating for multimode optical fibre, single-mode optical fibre with long-period grating (LPG) and planar optical waveguides. Thin DLC coatings significantly change sensing elements' properties. Constructed systems can be very sensitive to concentration changes of several chemical solutions (e.g. sodium chloride, calcium chloride and ethylene glycol) due to changes of refractive index of the solutions. The influence of Radio Frequency Plasma Chemical Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The LPG wavelength shift seems to depend more on the thickness of the DLC coating than on its refractive index. The DLC film can further act to stimulate the sensitivity of LPG structures to variations in the external refractive index [1]. To our knowledge, we have for the first time successfully deposited DLC coatings on tapered LPGs which can increase their application areas as fiber optic sensors.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The LPG wavelength shift seems to depend more on the thickness of the DLC coating than on its refractive index. The DLC film can further act to stimulate the sensitivity of LPG structures to variations in the external refractive index [1]. To our knowledge, we have for the first time successfully deposited DLC coatings on tapered LPGs which can increase their application areas as fiber optic sensors.…”
Section: Discussionmentioning
confidence: 98%
“…Previous works [1][2][3][4] have shown that DLC meets the requirements for smooth and hermetic coatings for optical fibers and can also significantly improve the sensitivity of optical fiber sensors. LPG has a wide range of applications, including band-rejection filters, gain flattening filters and sensors [1,[5][6][7][8][9][10][11][12][13]. During the last decade, various coatings for LPG have been presented [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Typically, dip-coating methods are applied for obtaining thin overlays around the fiber [5,6]. In our previous works, we have shown various nano-overlays deposited with radio-frequency plasma-enhanced CVD (RF PECVD) method on the LPGs [4,[7][8][9][10]. We have found that position of the sample in the plasma chamber has significant influence on thickness of the deposited overlay [9].…”
mentioning
confidence: 99%